Differences between Chemical Reaction Kinetics and Adsorption Kinetics: Fundamentals and Discussion - Tran, Hai Nguyen (Journal of Technical Education Science, 2022)
Adsorption kinetics is an essential part in adsorption studies. The pseudo-first-order (PFO) and pseudo-second-order (PSO) models are frequently used to model the experimental dataset of time-dependent adsorption. The differential equations (based on reaction rate and rate law) of the PFO and PSO models are similar to those of chemical reactions (i.e., first and second order-kinetic reactions). The adsorption kinetics is illustrated through the plot of qt (the amount of adsorbate adsorbed by adsorbent at time t) vs. time. This plot includes two important regions (kinetic and equilibrium). The adsorption rate constant (k1(PFO) or k2(PSO), respectively) of the PFO or PSO models needs to be calculated from two regions. The appropriate selection of initial adsorbate concentrations for studying adsorption kinetics should be based on adsorption isotherm to ensure that adsorption sites in adsorbent (material) are highly (nearly fully) covered by adsorbate (solute). Only in this case, the rate constant of the adsorption is accurately obtained.